2018
DOI: 10.1111/cas.13897
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexanone curcumin analogs inhibit the progression of castration‐resistant prostate cancer in vitro and in vivo

Abstract: Many prostate cancer patients develop resistance to treatment called castration‐resistant prostate cancer (CRPC) which is the major cause of recurrence and death. In the present study, four cyclohexanone curcumin analogs were synthesized. Additionally, their anticancer progression activity on CRPC cell lines, PC3 and PLS10 cells, was examined. We first determined their anti‐metastasis properties and found that 2,6‐bis‐(4‐hydroxy‐3‐methoxy‐benzylidene)‐cyclohexanone (2A) and 2,6‐bis‐(3,4‐dihydroxy‐benzylidene)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…In agreement with the findings of previous studies, Cur displayed higher levels of in vitro cytotoxicity against lung [20] and colon cancers than DZG [16]. Our previous study showed the IC 50 of Cur on PLS10 cells was 26.50 ± 1.80 µM, which was similar with this study [21]. This study confirmed that Cur induced G1 phase arrest via the inhibition of cyclin D1 expression in PLS10 cells, which is similar to the DZG treatment (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with the findings of previous studies, Cur displayed higher levels of in vitro cytotoxicity against lung [20] and colon cancers than DZG [16]. Our previous study showed the IC 50 of Cur on PLS10 cells was 26.50 ± 1.80 µM, which was similar with this study [21]. This study confirmed that Cur induced G1 phase arrest via the inhibition of cyclin D1 expression in PLS10 cells, which is similar to the DZG treatment (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
“…In our previous studies involving the cyclohexanone Cur analog, the replacement of β-diketone with the cyclohexanone group did not improve the pharmacokinetics of Cur [21]. However, in this study, we used DZG with a lack of β-diketone moiety (no other functional group replacements) and found that DZG could improve the pharmacokinetics and tissue distribution of Cur.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition to anti-proliferative and anti-apoptotic effects, anti-angiogenesis is one of the underlying mechanisms that can suppress the tumor growth and progression [28]. A range of natural or synthetic compounds inhibits cancer metastasis by blocking the formation of blood vessels [24,29,30]. In this study, the effect of PRE-HIF on the vessel numbers was not observed in PCai1 tumor.…”
Section: Discussionmentioning
confidence: 63%